Understanding client engagement in digital mental health interventions: An investigation of the eTherapy Attitudes and Process Questionnaire. Issue 9 (10th March 2022) - Clough, Bonnie; Yousif, Christina; Miles, Sasha; Stillerova, Sophia; Ganapathy, Aarthi; Casey, Leanne
Abstract: Aims: Digital mental health services may increase the accessibility and affordability of mental health treatments. However, client dropout a low use is often reported. The purpose of the current study was to investigate the structural validity of the e‐Therapy Attitudes and Process (eTAP) questionnaire, as a theoretically based (theory of planned behavior) tool for understanding ongoing client engagement intentions with digital mental health treatments. The possible role of eHealth literacy in predicting behavioral intentions to use digital mental health treatments was also examined. Methods: Participants were 244 Australian‐based adults aged between 18 and 56 years, who were currently using a digital mental health tool. Data were collected via online survey. Results: Confirmatory Factor Analysis was conducted, with good model fit obtained following two theoretically supported modifications. Moderated hierarchical regression supported the utility of the theory of planned behavior in predicting behavioral intentions, with attitudes emerging as a strong and consistent individual predictor. No support was found for the moderating role or individual significance of eHealth literacy. Conclusions: These findings support the clinical and research use of the eTAP as a theory‐based measure to understand client engagement in digital mental health interventions. The study also highlights the need for interventions to target attitudes to improve clients' ongoing engagement in digital mental health.